Similarities and differences in the experience of fatigue among people living with fibromyalgia, multiple sclerosis, ankylosing spondylitis and stroke. Issue 13 (7th February 2015) - Eilertsen, Grethe; Ormstad, Heidi; Kirkevold, Marit; Mengshoel, Anne M; Söderberg, Siv; Olsson, Malin
<x xml:space="preserve">Abstract</x> Aims and objectives To elucidate the experience of fatigue across several long‐term illnesses, focusing on the similarities and differences. Background Fatigue is common to many long‐term illnesses, but it has been studied mainly within the context of a single illness; qualitative studies comparing the experience and its impact on daily life across different long‐term illnesses are lacking. Design Qualitative design. Methods A secondary analysis was conducted of five original interview studies involving 95 persons with ankylosing spondylitis, fibromyalgia, multiple sclerosis or stroke. Results Similarities and differences concerning experiences of fatigue were found across the studied long‐term illnesses. All patients expressed the perception of having an unfamiliar body. Fatigue was also commonly expressed as unpredictable, uncontrollable and invisible to others. Differences were related to a constant versus a varying condition, a sudden and an uncontrollable sleepiness, a mutual reinforcement with pain and increased stress sensitivity. A lack of energy and a need for sleep and rest were common experiences, as was the impact on social relationships. There were also similarities regarding how the patients managed their daily life. The search for practical solutions and attitude adjustment differed with the fatigue characteristics. All patients felt a lack of understanding and disbelief from others. Conclusion and relevance to clinical practice Fatigue is commonly expressed by patients with long‐term illnesses. Variations in experience are related to the type of diagnosis. The disparity between experiences influences how patients managed and adjusted to the conditions of everyday life. The illness‐specific characteristics of fatigue warrant increased clinical awareness and may allow professionals to offer adequate information and establish effective methods of managing the condition. The feeling of invisibility and difficulty describing the experience of fatigue in particular highlights this need.